International Management of Sustainable Development: the Limits of the Necessary and the Possible - Yury N. Maleev (Московский журнал международного права, 2015)
Sustainable development in contemporary world supposes the increase of the role of international management by this process, where the role of international organizations, United Nations first of all, is specially increasing. The realization of this Concept is connected, among all, not only with the use of force in anti-crisis, anti-conflict measures, but in decision of acute political, social and ecological situations. Strict definition of what is objectively necessary and possible in such measures - is extremely acute contemporary problem.